Crossed ectopic kidney: prenatal diagnosis and postnatal follow‐up†. (13th June 2017) - Zajicek, Michal; Perlman, Sharon; Dekel, Benjamin; Lahav, Einat; Lotan, Danny; Lotan, Dor; Achiron, Reuven; Gilboa, Yinon
Abstract: Objective: The objective of this study is to investigate prenatal diagnosis and postnatal outcome of fetuses with crossed ectopic kidney. Method: Cases referred for an empty renal fossa and diagnosed with crossed ectopic kidney confirmed postnatally were analyzed retrospectively over a period of 10 years. Prenatal diagnosis was established following the detection of one kidney in a normal position and a second ipsilateral kidney fed by abnormal blood vessels on Doppler flow Results: Between 2005 and 2015, 185 fetuses were referred for an empty renal fossa. Crossed ectopic kidney was diagnosed in 10 of them. Associated congenital urological anomalies included two cases of double collecting system and bilateral hydronephrosis in one. Associated extra renal findings were single umbilical artery (4/10), ventricular septal defects (1/10), and persistent left superior vena cava (1/10). On postnatal follow‐up, bilateral vesicoureteral reflux was diagnosed in a case who presented prenatally with bilateral hydronephrosis and two cases of mild hydronephrosis. All cases were managed conservatively. Conclusion: Crossed ectopic kidney should be suspected in cases presenting with an empty renal fossa and a normal positioned kidney. Thorough anatomical scan should be performed as well as periodic follow‐up throughout pregnancy. Postnatal nephrological follow‐up is recommended. © 2017 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Crossed ectopic kidney is a rare developmental renal anomaly at which both kidneys are located on the same side of the midline. In children and adults, crossed ectopic kidneys are associated with pyelonephritis, hydronephrosis, and urolithiasis. What does this study add? In utero diagnosis of crossed ectopic kidney is feasible and should be suspected in a fetus presenting with an empty renal fossa. A favorable outcome is expected following a thorough normal anatomic scan. Postnatal nephrological follow‐up is recommended.